2002
DOI: 10.1038/modpathol.3880516
|View full text |Cite
|
Sign up to set email alerts
|

Antineutrophil Cytoplasmic Autoantibody in the Absence of Wegener's Granulomatosis or Microscopic Polyangiitis: Implications for the Surgical Pathologist

Abstract: Antineutrophil cytoplasmic antibodies (ANCA) are useful serologic markers for the diagnosis and management of patients with Wegener's granulomatosis (WG) and microscopic polyangiitis (MPA). However, problems in diagnosis and classification may occur when patients with other disorders develop ANCA. A 7-year review (1993-1999) disclosed 247 patients whose sera tested positively for ANCA by an indirect immunofluorescence method: 166 patients for cytoplasmic-ANCA (C-ANCA) and 81 patients for perinuclear-ANCA (P-AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 70 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…In CC, a tendency to increased anti-nuclear antibodies (ANA) was seen in one study, whereas increased levels of ANA, ANCA, and ASCA were seen in others [3], [4], [7]. One confounding factor may be that the level of auto-antibodies correlates with disease activity, and high values may only be detected in the active disease [10].…”
Section: Introductionmentioning
confidence: 98%
“…In CC, a tendency to increased anti-nuclear antibodies (ANA) was seen in one study, whereas increased levels of ANA, ANCA, and ASCA were seen in others [3], [4], [7]. One confounding factor may be that the level of auto-antibodies correlates with disease activity, and high values may only be detected in the active disease [10].…”
Section: Introductionmentioning
confidence: 98%
“…6 A previous report demonstrated that chronic interstitial lesions are common histologic features in patients with MPO-ANCA based on the pathologic reviews. 7,8 Thus, pulmonary fibrosis is now a recognized manifestation of MPA. Nada et al reported three patients initially diagnosed with idiopathic pulmonary fibrosis (IPF) that developed pulmonary-renal vasculitis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when ANCA is detected in IP with other organ involvement, it may be relatively easy to diagnose the disease as systemic vasculitis, such as GPA, MPA, and eosinophilic GPA [21,22]. In cases where the disease is limited to the lung, it is difficult to differentiate between ANCA-positive IP caused by the other etiology and GPA/MPA without surgical lung biopsy [23,24,25]. This has been proved by the following studies.…”
Section: Discussionmentioning
confidence: 99%
“…This has been proved by the following studies. First, 30% of the patients who had both positivity for MPO-ANCA or PR3-ANCA in sera test and active pulmonary disease underwent lung biopsy and were finally diagnosed with a disease other than GPA or MPO [25]. Second, separation of GPA from MPA is controversial [26].…”
Section: Discussionmentioning
confidence: 99%